Extensive proteomic remodeling is induced by eukaryotic translation elongation factor 1Bγ deletion in Aspergillus fumigatus. (30th September 2013) - O'Keeffe, Grainne; Jöchl, Christoph; Kavanagh, Kevin; Doyle, Sean
Abstract: The opportunistic pathogen Aspergillus fumigatus is ubiquitous in the environment and predominantly infects immunocompromised patients. The functions of many genes remain unknown despite sequencing of the fungal genome. A putative translation elongation factor 1Bγ (eEF1Bγ, termed elf A; 750 bp) is expressed, and exhibits glutathione S ‐transferase activity, in A. fumigatus . Here, we demonstrate the role of ElfA in the oxidative stress response, as well as a possible involvement in translation and actin cytoskeleton organization, respectively. Comparative proteomics, in addition to phenotypic analysis, under basal and oxidative stress conditions, demonstrated a role for A. fumigatus elfA in the oxidative stress response. An elfA ‐deficient strain ( A. fumigatus Δ elfA ) was significantly more sensitive to the oxidants H2 O2, diamide, and 4, 4′‐dipyridyl disulfide (DPS) than the wild‐type. This was further supported with the identification of differentially expressed proteins of the oxidative stress response, including; mitochondrial peroxiredoxin Prx1, molecular chaperone Hsp70 and mitochondrial glycerol‐3‐phosphate dehydrogenase. Phenotypic analysis also revealed that A. fumigatus Δ elfA was significantly more tolerant to voriconazole than the wild‐type. The differential expression of two aminoacyl‐tRNA synthetases suggests a role for A. fumigatus elfA in translation, while the identification of actin‐bundling protein Sac6 and vacuolar dynamin‐like GTPase VpsA link A. fumigatus elfA to the actin cytoskeleton. Overall, this work highlights the diverse roles of A. fumigatus elfA, with respect to translation, oxidative stress and actin cytoskeleton organization. In addition to this, the strategy of combining targeted gene deletion with comparative proteomics for elucidating the role of proteins of unknown function is further revealed.